Adoption and perception of farm management information systems by future Swiss farm managers – An online study. (January 2022) - Ammann, Jeanine; Walter, Achim; El Benni, Nadja
Abstract: The use of digital technologies in agriculture offers various benefits, such as site-specific application, better monitoring, and physical relief. The handling of these technologies requires a specific skill set. Therefore, the question arises of when and how farm managers learn about digital technologies. Aiming to analyse the current situation, the present research investigated the role that digital technologies play in vocational training for future farm managers. Taking the example of farm management information systems (FMIS), the present study also analysed various predictors of adoption, including the effect of training. To investigate these research questions, an online survey among teachers and students of the farm management vocational programme across Switzerland was conducted in the spring of 2021. In total, 150 individuals participated, 41 of whom were teachers. Participants answered questions about the learning content in the farm management programme and their perception of digital technologies in general. Students further reported whether they already had a farm they would be managing in the future and how they perceived FMIS. The results indicate that both teachers and students are convinced that digital technologies play an important role in agriculture and will gain more importance in the future. A substantial part of 43% of the students who participated indicated that they had learned neither about digital technologies during their basic agricultural training nor the subsequent farm management programme. In terms of FMIS, 51% of the student sample indicated that they had never heard about FMIS during their agricultural training. While having learned about FMIS was not a significant predictor for adoption, gender, perceived ease of use, and intention to use more digital technologies in the future significantly predicted the adoption of FMIS. The paper concludes that, to support the adoption of digital technologies and FMIS specifically, training for future farm managers should focus on how to operate an FMIS to increase the perceived ease of use of this technology. Graphical abstract: Image 1 Highlights: 57% of the students learned about digital technologies during vocational school. 49% of the students learned about FMIS during vocational school. Intention to use digital technologies is an important predictor for the TTMA. Perceived ease of use of FMIS is an important predictor for the TTMA.